NUTRIENT COMPOSITION AND TOTAL TRACT NUTRIENT DIGESTIBILITY COEFFICIENT OF SAGO (PUTAK MEAL) FROM DIFFERENT LOCATION - Catootjie L. Nalle; Helda Helda; Fransiska Babo Lelu; Emilius Y. Bai (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The aim of the study was to evaluate the proximate composition and nutrient digestibility of sago meal from different origin on growing broilers. The experimental design used was randomized complete design consisting of five treatments and four replications. A total of 100 growing broilers were randomly distributed to 20 cages (5 birds/cage). Corn-soybean basal diets were formulated and then the assay diets were developed by substituting sago meal 20% (w/w) of the basal diets. The results showed that location significantly affected (P < 0.05) the crude protein (CP) and crude fibre (CF) contents of sago, but it did not affect (P > 0.05) the ash and gross energy contents. The digestibility coefficient (DC) of crude lipid (CL), CF and energy of sago were significantly affected (P < 0.05) by location. There were no differences (P > 0.05) on DCCL of sago meal from Lili dan Naibonat and between Naibonat and Pariti. The DCCL of Bipolo sago meal was not different (P > 0.05) from DCCL of Lili sago meal, however, it was significantly different (P < 0.05) from the DCCL of sago from Naibonat and Pariti. The DCCF of Naibonat sago was significantly different (P < 0.05) from the DCCF of sago from Pariti, Bipolo and Lili. The DCE of Naibonat sago was significantly higher (P < 0.05) that that of Pariti and Bipolo sago. In conclusion, 1) the nutrient composition and digestibility of sago meal were affected by the different origin; 2) sago is potential to be used as energy source feed ingredient in poultry diet due to its high energy content.